The Structure of Teacher’s Directives of the English Lecturers of Muhammadiyah University Semarang - Rr. Dewi Wahyu Mustikasari (IAIN Salatiga, 2011)
Teacher’s directive is an interesting item to discuss since it can be elaborated into command, order, request, and advice. Furthermore, it can be developed that teacher’s directive has several structures. The structure of teacher’s directives can be classified into three kinds: imperative, interrogative, and declarative. I would like to discuss about the various forms by which directives are realized in the classroom in this study. The subjects of the study were 10 English lecturers of Muhammadiyah University Semarang. The instrument of the study is DCT questionnaires, which is consisted of 10 certain situations. The result shows that most of the subjects of study prefer to produce declarative with 74 utterances (50%). Second, they choose imperative with 50 utterances (34%). Next, they construct interrogative with 23 utterances (16%). Declaratives provide powerful directives than the other types. Declaratives gain an explicit expression. Teachers like to use declaratives, since declaratives are understandable. It will minimize the misinterpretation from the students.keywords; illocutionary act; directives; teacher’s directives; the structure of teacher’s directives.